Estimate of tsunami source using optimized unit sources and including dispersion effects during tsunami propagation: The 2012 Haida Gwaii earthquake. Issue 18 (23rd September 2016) - Gusman, Aditya Riadi; Mulia, Iyan Eka; Satake, Kenji; Watada, Shingo; Heidarzadeh, Mohammad; Sheehan, Anne F.
Abstract: We apply a genetic algorithm to find the optimized unit sources using dispersive tsunami synthetics to estimate the tsunami source of the 2012 Haida Gwaii earthquake. The optimal number and distribution of unit sources gives the sea surface elevation similar to that from our previous slip distribution on a fault using tsunami data, but different from that using seismic data. The difference is possibly due to submarine mass failure in the source region. Dispersion effects during tsunami propagation reduce the maximum amplitudes by up to 20% of conventional linear longwave propagation model. Dispersion effects also increase tsunami travel time by approximately 1 min per 1300 km on average. The dispersion effects on amplitudes depend on the azimuth from the tsunami source reflecting the directivity of tsunami source, while the effects on travel times depend only on the distance from the source. Key Points: Comparison of the source models from tsunami and seismic data suggests a possible submarine mass failure during the earthquake The tsunami dispersion effects on amplitudes depend on azimuth from the tsunami source, reflecting the directivity of tsunami source Longwave simulation yields shorter travel times than the more accurate dispersive wave by 1 min for every 1300 km on average